Social Media And Political Accountability: Spotlighting the Roles Of X (Twitter) and Instagram in Anti-Corruption Activism in Nigeria - Desmond Onyemechi Okocha; Hassan Aliyu Karofi; John Vendaga; Michael Faloseyi (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
This study examined the roles of social media, notably X (formerly Twitter) and Instagram, in exposing political corruption and supporting justice advocacy in Nigeria. In a context where traditional media are constrained by censorship and political control, digital activism on these platforms has become central to holding public officials to account. Guided by Social Accountability Theory and the Digital Activism Framework, the study adopted a quantitative, cross-sectional survey design and a structured questionnaire comprising four Likert-type scales (five-point, from strongly disagree to strongly agree) that captured perceived roles of X and Instagram in corruption exposure, justice-advocacy strategies, challenges, and policy options. Using stratified random sampling, 500 Nigerian users of X and Instagram, journalists, and justice advocates were selected across the four strata and their responses analysed with descriptive statistics and correlation analysis. The findings show that between 80.0% and 82.8% of respondents agreed that X and Instagram are effective for exposing political corruption and that scandals publicised on these platforms influence public opinion and can trigger investigations and legal action (mean scores around 4.0 on a five-point scale, standard deviations of about 1.1). Similarly, around four-fifths of respondents supported integrating social media into official anti-corruption efforts and improving platform algorithms to prioritise credible anti-corruption content (mean = 3.94–4.00). Government restrictions, algorithmic suppression, and misinformation emerged as major barriers to effective digital accountability. The study concludes that X and Instagram now function as critical infrastructures of social accountability in Nigeria and recommends institutionalised collaboration between anti-corruption agencies, digital activists, and civil society organisations, as well as investments in digital literacy, evidence-based regulation of misinformation, and greater algorithmic transparency.